Belize : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This Selected Issues paper analyzes macro-financial linkages for Belize. The banking system in Belize is facing significant challenges that could have a negative impact on the wider economy. Under adverse scenarios, the loss of correspondent banking relationships (CBRs) could have a sizeable impact on Belize's economy and financial stability as fewer CBRs, different local banks' business models, or stricter due diligence requirements could kick many economic agents out of formal trade and finance channels. Threats to the financial system, including those related to money laundering and terrorist financing, should be tackled on multiple fronts, including through closer coordination with regional and global public and private partners.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet